2004
DOI: 10.1080/03605310490514234
|View full text |Cite
|
Sign up to set email alerts
|

The European Embryonic Stem-Cell Debate and the Difficulties of Embryological Kantianism

Abstract: As elsewhere, the ethical debate on embryonic stem cell research in Central Europe, especially Germany and Switzerland, involves controversy over the status of the human embryo. There is a distinctive Kantian flavor to the standard arguments however, and we show how they often embody a set of misunderstandings and argumentative shortcuts we term "embryological Kantianism." We also undertake a broader analysis of three arguments typically presented in this debate, especially in official position papers, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As did others, we have shown that considering early embryos as the moral equivalent of people raises unsurmountable difficulties, in part because the earliest stages of human development do not possess the biological underpinnings of numerical identity [10,11]. Furthermore, the search for a defined moment in prenatal development at which moral standing accrues to the embryo/foetus is probably a wild goose chase [12].…”
Section: The Ethical and Legal Debate About Pgdmentioning
confidence: 96%
“…As did others, we have shown that considering early embryos as the moral equivalent of people raises unsurmountable difficulties, in part because the earliest stages of human development do not possess the biological underpinnings of numerical identity [10,11]. Furthermore, the search for a defined moment in prenatal development at which moral standing accrues to the embryo/foetus is probably a wild goose chase [12].…”
Section: The Ethical and Legal Debate About Pgdmentioning
confidence: 96%
“…But this makes their position more fragile, because it depends on the promises of adult stem cells, which need to turn out as they wish them to be. Third, if we do not believe that a human early blastocyst has a standing comparable to that of a human person, for instance because we realize that this is impossible to prove on the basis of general secular arguments, 9 then the ethical divide between embryonic and adult stem cells largely vanishes.…”
Section: Embryonic Vs Adult Stem Cells and The Politics Of Hopementioning
confidence: 98%
“…The main focus of their essay is a critique of a middle position concerning the status of the embryo called the respect model. This position assigns to the embryo "some form of intrinsic value that commands respect without preventing all forms of killing of early embryos" (Mauron & Baertschi, 2004). This means that the notions of respect and human dignity play a crucial role in the debate, and find their roots in the Kantian sense of dignity.…”
Section: The Boundaries Of Common Groundmentioning
confidence: 99%